The effect of message credibility on media use and perception of fake news among students - Ahmad Elyass Hussain, Souhaila; Kilagwa, Rehema; Mohd Zaali, Yusnita; Wok, Saodah (Communication Department, Faculty of Modern Languages, Universiti Putra Malaysia, 2018)
Fake news is a major concern globally. Numerous news articles worldwide have reported on the spread of fake news in multiple arenas. Malaysia, similarly, has been covering the proliferation of fake news in the media. A Fake News Bill was passed in Parliament, at record time, in the hope of attaining preventive measures to counter the spread of fake news (the bill was repealed four months later). This study aims to determine students’ perception of fake news in the context of their media usage and message credibility. Specifically, it aims to determine the relationship between media use, message credibility and perception of fake news; and to analyse the mediating effect of message credibility on media use and the perception of fake news. Fake news, in this context, is defined as deliberate misinformation spread by traditional or social media. The research utilizes the Media Dependency Theory in explaining the relationship between the audiences, media and the larger social system. The theoretical framework assumes that during times of conflict or uncertainty, in this case before the General Election 2018, audiences are likely to be more dependent on the media for information. It employs a quantitative research design using the survey method. 237 students from the Department of Communication, International Islamic University Malaysia (IIUM) participated in the study. Findings show that there are significant relationships among media use, message credibility and fake news. The Media Dependency Theory is supported in this study.